The Ministry of Religious Affairs' Role via Preachers in Strengthening Religious Moderation within a Muslim Community of Diverse Islamic Organizational Affiliations in Ngunut Village - Septian Dwi Cahyo; Dzulfikar Akbar Romadlon (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study analyzes the strategy of the Ministry of Religious Affairs through a field preacher in strengthening religious moderation in Ngunut Village, Karanganyar. The case concerns intra-Muslim diversity represented by Nahdlatul Ulama, Muhammadiyah, LDII, and MTA rather than interreligious plurality. A qualitative case-study design combined participant observation, semi-structured interviews, and document analysis. The researcher was positioned as a participant-researcher; therefore, personal field experience was treated as reflective data and corroborated with institutional documents, local religious actors, and community accounts. The findings show that the Ministry's moderation mandate was translated through layered coordination involving the district Ministry office, the Religious Affairs Office, religious counselors, the village government, mosque administrators, and Islamic organizations. The preacher worked across mosques, Qur'anic classes, schools, inter-organizational forums, and social services by adapting language, methods, and roles to different audiences. Religious moderation was sustained through recognition of organizational differences, deliberation, rotating leadership in communal worship, accommodation of differences in subsidiary religious practices, and public-oriented social action. Bil-hal practices of the four organizations—education, charity, hospitality, sacrificial-meat distribution, health services, environmental activities, and an open MSME bazaar—provided shared arenas without erasing organizational identity. From an Islamic Religious Education perspective, the process reflects non-formal value education through teaching, exemplary conduct, habituation, dialogue, and social participation. The study concludes that the Ministry did not create moderation from an initially conflictual setting; it strengthened an existing social ecology through an educational, adaptive, collaborative, and integrative strategy